Analysis of Attributes and Dimensions of the Built Environment Quality from the Perspective of Employees from Furniture Companies - Gabriel Sperandio Milan; Marcelo Benetti Correa da Silva; Suélen Bebber (BBR: Brazilian Business Review)
The analysis of the attributes and dimensions of the built environment quality (workspace) of companies is relevant, because it is associated to the expectations and perceptions of their employees and re lated to its satisfaction, productivity and business performance. Thus a survey research was implemented in five furniture companies, located inside the Rio Grande do Sul state, focusing on identifying the dimensions of the quality of the built environments analyzed, and their respective attributes, using as a basis previous studies of the area. Unlike the literature, the study identified seven dimensions of the built environment quality (configuration, appearance, functionality, specific activities, person al relationships, company location and comfort), composed of thirty - one attributes. It was also observed the overall satisfaction of employees of these companies in relation to the work environment, which resulted in a rate of 66.00%.